Dynamic Maceration of Acerola (Malpighia emarginata DC.) Fruit Waste: An Optimization Study to Recover Anthocyanins - Cerino, María Carolina (2023)
Acerola (Malpighia emarginata DC.) is a tropical fruit with a vibrant red color attributed toanthocyanins, natural pigments, with several applications in the food, nutraceutical, and cosmeticindustries. Therefore, the suitability of acerola fruit waste for producing anthocyanin colorants bydynamic maceration was investigated. The extraction process was optimized by combining the factors time (2–90 min), temperature (20–90 C), and ethanol percentage (0–100%) in a central composite rotatable design (CCRD) coupled with response surface methodology (RSM). The extraction yield determined by a gravimetric method and the levels of cyanidin-O-deoxyhexoside and pelargonidin-Odeoxyhexoside anthocyanins quantified in the 20 run extracts by HPLC-DAD were used as dependent variables. After fitting the experimental data to a quadratic equation, the obtained statistically valid predictive models were used to determine optimal macerating conditions. Under global settings (25 min processing at 41 C with 12% ethanol), the extraction yielded 57.1% (w/w) and each gram of extract contained 2.54 mg of anthocyanins. Overall, this study highlights the renewable potential of acerola fruit waste for obtaining natural anthocyanin extracts that could represent a sustainable alternative to artificial colorants used in food and other products.